Manhaj Abdullāh Ibn Fūdī fī Iḥtiṣāri Tafsīrihi “Ḍiyā' al-Taʾwīl fī Ma'āni al-Tanzīl" to "Kifāyat Du'afāʾ al-Sūdān fī Bayān Tafsīr al-Qurʾān” - Tahir, Tahir Harun; Elhut, Mücahit (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This study aims to introduce Abdullah ibn Fodio and his works, with a particular focus on his approach to summarizing the tafsir of “Ḍiyāʾ al-Taʾwīl fī Maʿāni al-Tanzīl” to “Kifāyat Du’afāʾ al-Sūdān fī Bayān Tafsīr al-Qurʾān”, using Juz Amma as the focus of the research. This researcher is qualitative with a type of literature study. The research uses an interpretation approach. The data collection technique uses documentation. The data analysis uses content analysis. The results of the study say that “Ḍiyāʾ al-Taʾwīl” is one of the most important works of Abdullah ibn Fodio in the field of tafsīr, which he compiled based on various tafsīr books. The study results say that his interpretation of "Ḍiyāʾ al-Taʾwīl fī Maʿāni al-Tanzīl" is a linguistic interpretation to some extent and is based on several interpretations, making it very important in northern Nigeria. As for " Kifāyat Du’afāʾ al-Sūdān" is an abbreviation of the broad topic described in the previous interpretation. It enjoys narrative ease and simplification by focusing on the intended goals and some of Israel's stories and effects. The interpretation of " Ḍiyāʾ al-Taʾwīl fī Maʿāni al-Tanzīl" is suitable for researchers and advanced science students with experience and the ability to absorb details. At the same time, "Kifāyat Du’afāʾ al-Sūdān" is suitable for novice science students, as its simple and concise style characterizes it without digging into the details, making it one of the most prominent interpretations spread across northern Nigeria.